Hepatitis B Vaccination Induced TNF-α- and IL-2-Producing T Cell Responses in HIV− Healthy Individuals Higher than in HIV+ Individuals Who Received the Same Vaccination Regimen - Kriangkrai Chawansuntati; Kanokporn Chaiklang; Romanee Chaiwarith; Jutarat Praparattanapan; Khuanchai Supparatpinyo; Jiraprapa Wipasa (Journal of Immunology Research)
We investigated cytokine production and expression of degranulation marker CD107a after different strategies of hepatitis B virus (HBV) vaccination in human immunodeficiency virus-infected individuals, which were three doses of 20 μg (standard dose group), four doses of 20 μg (four doses group), or four doses of 40 μg (four double doses group), compared to standard dose vaccination in healthy controls. PBMCs collected at different time points were stimulated in vitro with recombinant hepatitis B surface antigen and analyzed by flow cytometry. There was an increase in TNF-α production of total and memory CD4+ T cells at 7 months after vaccination in healthy controls compared to the HIV+ group, which received the same standard vaccination regimen. An increase in the IL-2-producing memory CD4+ T cells in the healthy control group was also observed at 7 months after vaccination. No differences were observed between the healthy controls and both groups of four doses at any time point of study. These results suggest that the standard HBV vaccination schedule might induce better production of TNF-α and IL-2 from CD4+ T cells in healthy individuals. Modification of HBV vaccination schedule by increasing the frequency and/or dosage may improve the CMI response in HIV-infected individuals. This trial is registered with NCT1289106.